Character Education Strengthening Strategy Based On School Culture For Senior High School Students - Jamaludin, Sophan; Wasliman, Iim; Rostini, Deti; Helmawati, Helmawati (CV. Inara, 2022)
The era of globalization characterized by free competition and excellence, and supported by modern information technology, turned out to provide problems for the world of education in the development of the character of the nation. Among the problems is the optimal involvement of envirormental input consisting of families, communities and stakeholders, to the process of implementing strengthening character education strategies based on humanist education principles. Based on some of these problems, the study focused on: